2010
DOI: 10.1080/10683160802698766
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of offending-related stage of change in offenders: psychometric validation of the URICA with male prisoners

Abstract: Measuring accurately an offender's present stage of change on offending-related needs may be important for determining match with Á and therefore selection into Á rehabilitation programmes. It is also essential testing empirically the dominant model of offending-related behavioural change Á the Transtheoretical Model (TTM). Several self-report questionnaire scales and algorithms have been developed and applied to offender populations to measure stage of change. The paper reports on an investigation into the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 73 publications
1
25
0
4
Order By: Relevance
“…The factorial validity of the URICA is even harder to ascertain in offending samples given the paucity of studies in this area. To date, only two studies on general offenders have found support for a four-factor structure (Levesque, Gelles, & Velicer, 2000;Polaschek et al, 2010). Using a domestic violence adaptation of the URICA, an earlier study by Levesque et al (2000) on 258 domestic violence offenders supported this four-factor structure.…”
Section: Methodsmentioning
confidence: 74%
See 4 more Smart Citations
“…The factorial validity of the URICA is even harder to ascertain in offending samples given the paucity of studies in this area. To date, only two studies on general offenders have found support for a four-factor structure (Levesque, Gelles, & Velicer, 2000;Polaschek et al, 2010). Using a domestic violence adaptation of the URICA, an earlier study by Levesque et al (2000) on 258 domestic violence offenders supported this four-factor structure.…”
Section: Methodsmentioning
confidence: 74%
“…Using a domestic violence adaptation of the URICA, an earlier study by Levesque et al (2000) on 258 domestic violence offenders supported this four-factor structure. The study by Polaschek et al (2010) reported cautious support for the four-factor structure with a non-normed fit index of .96 and a comparative fit index (CFI) of .97, but did not report the value for the root mean square error of approximation (RMSEA). Other studies involving the offending population found support for fewer than four factors (Cohen et al, 2005;Eckhardt, Babcock, & Homack, 2004;Eckhardt & Utschig, 2007;Hemphill & Howell, 2000;Kim & Song, 2009).…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations